Neural Response to Low Energy and High Energy Foods in Bulimia Nervosa and Binge Eating Disorder: A Functional MRI Study - Donnelly, Brooke; Foroughi, Nasim; Williams, Mark; Touyz, Stephen; Madden, Sloane; Kohn, Michael; Clark, Simon; Sachdev, Perminder; Peduto, Anthony; Caterson, Ian; Russell, Janice; Hay, Phillipa (Frontiers in Psychology, 2022)
Objective: Binge eating episodes are a transdiagnositic feature of eating disorders such as bulimia nervosa (BN) and binge eating disorder (BED). Neuroimaging research of the responses of those with recurrent binge eating to disorder-specific stimuli such as food, is limited. Furthermore, to our knowledge there have been no previous published studies examining the neural response of individuals currently experiencing binge eating, to low energy foods. Our objective was to examine the neural responses to both low-energy and high-energy food images in three emotive categories (disgust; fear; happy) in BN and BED participants. Methods: Nineteen females with BN (n= 14) or BED (n=5), comprising the binge eating group (BEG) (N=19), and nineteen age-matched HC’s completed thorough clinical assessment prior to functional magnetic resonance imaging (fMRI). Neural response to low-energy and high-energy foods and non-food images was compared between groups using whole-brain exploratory analyses, from which six regions of interest (ROI) were then selected: frontal, occipital, temporal, and parietal lobes; insula and cingulate. Results: In response to low energy food images, the BEG demonstrated differential neural responses to all three low energy foods categories (disgust; fear; happy) compared to HCs. Correlational analyses found a significant association between frequency of binge episodes and diminished temporal lobe and greater occipital lobe response. In response to high energy food images, compared to HC’s, the BEG demonstrated significantly decreased neural activity in response to all high energy food images. The HC’s had significantly greater neural activity in the limbic system, occipital lobe, temporal lobe, frontal lobe and limbic system in response to high energy food images. Conclusion: Results in the low energy food condition indicate that binge frequency may be related to increased aberrant neural responding. Furthermore, differences were found between groups in all ROI’s except the insula. The neural response seen in the BEG to disgust food images may indicate disengagement with this particular stimuli. In the high energy food condition, results demonstrate that neural activity in BN and BED patients decreases in response to high energy foods, suggesting disengagement with foods that may be more consistent with those consumed during a binge eating episode.